2005
DOI: 10.1158/0008-5472.can-04-2214
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antitumor Response of Interleukin 2 with Melphalan in Isolated Limb Perfusion in Soft Tissue Sarcoma–Bearing Rats

Abstract: The cytokine interleukin 2 (IL-2) is a mediator of immune cell activation with some antitumor activity, mainly in renal cell cancer and melanoma. We have previously shown that tumor necrosis factor (TNF)-A has strong synergistic antitumor activity in combination with chemotherapeutics in the isolated limb perfusion (ILP) setting based on a TNF-mediated enhanced tumor-selective uptake of the chemotherapeutic drug followed by a selective destruction of the tumor vasculature. IL-2 can cause vascular leakage and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…These findings led to our search for alternative agents with known vascular permeability increasing activity, such as histamine and interleukin-2. We have shown that these agents also enhance drug accumulation in the tumor resulting in synergistic antitumor activity in an isolated setting (13,44). Apparently, this dual approach consisting of a combination of tumor cell-and tumor vasculature-directed therapy is an important concept for a good tumor response.…”
Section: Discussionmentioning
confidence: 98%
“…These findings led to our search for alternative agents with known vascular permeability increasing activity, such as histamine and interleukin-2. We have shown that these agents also enhance drug accumulation in the tumor resulting in synergistic antitumor activity in an isolated setting (13,44). Apparently, this dual approach consisting of a combination of tumor cell-and tumor vasculature-directed therapy is an important concept for a good tumor response.…”
Section: Discussionmentioning
confidence: 98%
“…Promising findings have been reported for histamine [164,165], interleukin 2 [166] and the nitric oxide synthase inhibitor L-NAME [167]. Improved response rates have also been reported following the upregulation of endothelial monocyte-activating polypeptide II (EMAP-II) in extremity soft tissue sarcomas [168].…”
Section: Future Perspectivesmentioning
confidence: 97%
“…In particular, in rat models of isolated limb perfusion -a technique used to deliver high doses of drugs into the bloodstream of a limb -coadministration of chemotherapeutic drugs with biomolecules able to affect the integrity of the endothelial lining of vessels, such as TNFa, histamine, or IL-2, can increase drug penetration in tumors [55][56][57]. Remarkably, the addition of TNF-a to regional isolated limb perfusion with melphalan or doxorubicin also produces response rates higher than those obtained with chemotherapy alone in patients with softtissue sarcomas or melanomas [58].…”
Section: Reviewmentioning
confidence: 99%